Shakarim Kudaiberdiev, Kalkaman-Mamyr, Enlik-Kebek, tradition, freedom, morality, humanism, philosophical poetry. (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2025)
This article provides a detailed examination of the interrelation between the concepts of tradition and innovation based on the poems Kalkaman-Mamyr and Enlik-Kebek by the prominent Kazakh writer Shakarim Kudaiberdiev. Through the analysis of these works, the author reveals the poet’s attitude toward the moral and spiritual values of society, as well as his philosophical reflections on human destiny and individual freedom. The poems artistically depict the contradictions between the restrictive nature of ancient customs and clan relations and the individual’s aspiration for personal liberty. The study employs historical-comparative, textological, and hermeneutic methods, which allow for a comprehensive analysis of the ideological content, artistic system, and compositional structure of the works. Shakarim’s creations, reflecting the process of socio-spiritual renewal in Kazakh society, affirm humanistic and ethical values. The poet expands the boundaries of traditional epic poetics, elevating the themes of human existence, love and fidelity, justice and honor to a new philosophical level. The article also outlines Shakarim’s creative evolution and his role in continuing Abai’s literary tradition. The research demonstrates the significance of Kalkaman-Mamyr and Enlik-Kebek as the origins of innovation in Kazakh literature. It is emphasized that Shakarim’s humanistic ideas and reflections on personal freedom remain relevant for contemporary literary studies.